PENGARUH PEMBELAJARAN BLENDED LEARNING MENGGUNAKAN APLIKASI MICROSOFT POWER POINT TERHADAP PEMAHAMAN HIMPUNAN - Rika Anggita Hasibuan; adek Nilasari Harahap; Puspa Riani Nasution; Nova Christina Dewi (Jurnal Cermatika, 2024)
This research aims to determine the influence of learning in understanding associations through the Blended Learning learning model in class VII of SMP N 5 East Angkola for the 2023/2024 academic year. In this study, the sample was taken from the population using simple random sampling, namely the researcher took the sample randomly without paying attention to the strata in the population. This type of research is Quasi Experimental Research. The research subjects were class VII-2, totaling 20 people. There were 13 women and 6 men. The instrument used is a test. The test used is an essay form test with 5 questions. For final data analysis using Simple Linear Regression. The constant (a) is 12.694, meaning that if the Blended Learning influence level variable is 0, then the learning outcome volume variable has a value of 12.694. The regression coefficient for the Blended Learning variable has a positive value of 36.863, indicating that if it increases, there will be an increase of 36.863. The coefficient has a positive value, meaning that there is a positive relationship between Blended Learning and Microsoft Power Point.